Karakterisasi dan Optimasi Aktivitas Bakteriosin Isolat Bakteri Asam Laktat LG-90 Asal Sedimen Mangrove Pantai Logending - Mayliani, Fiqita; Kusharyati, Dyah Fitri; Ryandini, Dini (BioEksakta : Jurnal Ilmiah Biologi Unsoed, 2022)
Lactic acid bacteria (LAB) are a group of Gram-positive bacteria that produce various active metabolites, including lactic acid, ethanol, hydroperoxides, and bacteriocins. Bacteriocin is a peptide that has a broad spectrum to inhibit the growth of pathogenic microbes. The ability of bacteriocins to inhibit microbial growth is influenced by various factors, including the concentration of antimicrobial substances, temperature, storage time, pH, and microbial properties. LG-90 isolated from mangrove sediments at Logending Beach located in Ayah Village, Ayah District, Kebumen Regency, is known to be capable of producing bacteriocins. This research aimed to determine the characteristics and identity of LG-90, the optimum time of bacteriocin production, and the optimum pH and temperature for bacteriocin activity of LG-90 as antimicrobial agents. This research used a survey method. The independent variable in this research was LAB LG-90 isolates and the dependent variable were the ability to produce bacteriocins and their antibacterial power. The main parameter observed was diameter of the inhibition zone and the supporting parameters were morphological, physiological, and biochemical properties of bacteria. Descriptive data analysis and characterization of bacterial isolates refers to Bergey’s Manual of Systematic Bacteriology. The results showed that LG-90 from the mangrove sediments of Logending Beach had the similar phenetic characters as the genus Lactobacillus. Optimum bacteriocin production of LG-90 at an incubation time of 16 hours. Optimum antimicrobial activity of LG-90 bacteriocin at pH 6 and heating temperature of 40oC.